Peripheral Blood MDSCs, IL-10 and IL-12 in Children with Asthma and Their Importance in Asthma Development - Zhang, Yan-Li (Public Library of Science, 2013)
OBJECTIVE: To investigate myeloid-derived suppressor cell (MDSC) accumulation and interleukin 10 (IL-10) and interleukin 12 (IL-12) levels during the onset of asthma in both pediatric patients and mouse models, as well as their possible roles in the development of asthma. METHODS: Peripheral blood samples were gathered from children with asthma attacks (attack group) and alleviated asthma (alleviated group), as well as two control groups, children with pneumonia and healthy children. The pathological characteristics of asthma in asthmatic mice, budesonide-treated asthmatic mice, and normal control mice were also evaluated by immunohistochemistry (IHC) and hematoxylin and eosin (H&E) staining. RESULTS: MDSC accumulation and serum IL-10 levels were significantly elevated in the children with asthma compared with the budesonide-treated alleviated group, normal healthy controls, and pneumonia controls (p<0.05), whereas those in the latter three groups showed no statistical differences (p>0.05). The level of serum IL-12 in the asthmatic children was drastically reduced compared to the budesonide-treated alleviated group, healthy controls, and pneumonia controls (p<0.05), whereas the latter three groups showed no significant differences in their serum IL-12 levels. The percentage of MDSCs in children with asthma was positively correlated with the level of serum IL-10 and negatively correlated with the level of serum IL-12. The levels of MDSCs and IL-10 in asthmatic mice were significantly higher than those in the normal control mice (both p<0.05) and were reduced after budesonide treatment (both p<0.05). IL-12 expression in the asthmatic mice was significantly lower than the control and was increased upon budesonide treatment (both p<0.05). CONCLUSION: During the onset of asthma, the accumulation of MDSCs and the level of serum IL-10 increase, while the level of IL-12 decreases. These fluctuations may play an important role in the development of asthma.